TIPOLOGI WAJAH BANGUNAN KOLONIAL GEREJA KATOLIK ROMA DI SEMARANG - Praha Prayogo, Gregorius Gravido; Pandelaki, Edward Endrianto; Harsritanto, Bangun Indrakusumo Radityo (Jurnal Arsitektur ARCADE, 2023)
Abstract: The Roman Catholic Church in Semarang has interesting things as an object of research because it has own uniqueness as one of the Cultural Heritage buildings that has a connection with the history of the city of Semarang, on the other hand various problems about socially, economically and culturally. As time progresses, the Gedangan Church and the Cathedral Church began to experience improvements due to the climate and the situation in the city of Semarang. The typology or characteristics of the two churches has several changes based on field studies of the two churches. Field studies and grouping of the characteristics of the buildings were carried out to answer the research, with the hope that the characteristics of the two churches can be preserved amidst cultural developments.Keyword: Architectural Typology, Roman Catholic Church, Cultural Heritage Abstrak: Gereja Katolik Roma di Semarang memiliki hal yang menarik untuk dijadikan obyek penelitian karena memiliki keunikan tersendiri sebagai salah satu bangunan Cagar Budaya yang memiliki keterkaitan dengan sejarah kota Semarang, disisi lain muncul berbagai permasalahan baik secara sosial, ekonomi dan budaya. Seiringnya berkembangnya waktu, Gereja Gedangan dan Gereja Katedral mulai megalami perbaikan akibat iklim serta situasi di kota Semarang. Tipologi atau karateristik dari kedua Gereja tersebut mengalamai beberapa perubahan berdasarkan studi lapangan pada kedua Gereja tersebut. Studi lapangan dan pengelompokkan karakteristik dari bangunan dilakukan untuk menjawab penelitian, dengan harapan karakteristik dari kedua Gereja tersebut dapat dilestarikan di tengah perkembangan budaya.Kata Kunci: Tipologi Arsitektur, Gereja Katolik Roma, Cagar Budaya